Foreign Language Anxiety in ICT-Based English Learning Context - Maximilian, Aksendro; Ajeng, Galuh Dwi; Safitri, Isnaini Amanda (Universitas Pamulang, 2026)
This study aims to investigate the levels of foreign language anxiety experienced by high school students and to identify the sources of anxiety in ICT-based English learning context. This research employed a descriptive qualitative method involving eleventh-grade students of SMAN 7 Bandar Lampung. Data were collected through the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and semi-structured interviews. Thirty students participated in the questionnaire, while five students were selected for in-depth interviews to explore their perceptions and experiences. The data were analyzed descriptively to reveal patterns of anxiety and its contributing factors. The findings indicate that most students experience moderate to high levels of foreign language anxiety in ICT-based learning environments. A significant number of students fall into the “anxious” and “very anxious” categories, suggesting that ICT integration does not entirely reduce anxiety. Interview results reveal that while some students feel motivated and enthusiastic about ICT-based learning, many struggle with lack of self-confidence, fear of making mistakes, technical difficulties, unfamiliarity with digital platforms, and the pressure of fast-paced online lessons. These factors collectively intensify students’ anxiety during foreign language learning. In conclusion, the study highlights that although ICT provides valuable support for English learning, it also introduces new sources of anxiety. Therefore, teachers need to implement supportive strategies, provide clear guidance, and create a less threatening digital learning environment to help students manage foreign language anxiety effectively.